Priorities in Biotechnology Research in Vietnam - Quy, Tran Duy; Vinh, Do Nang (International Service for National Agricultural Research, 2001)
Vietnam is an agricultural country with over 70% of the population involved in agricultural production. In 1991-1993, the growth rate of the national economy was 7.2% on average. The active development of the country was observed in all economic fields, including agriculture, industr y, imports and exports. In the same period, foreign investment in Vietnam increased by 50% each year. This favorable national development was due to the economic reforms and to the government's open-door policy. The investments for science, technology and environmental protection are considered to be the basis of economic growth and the sustainable future development of Vietnam. The objectives for agricultural development by the year 2000 in Vietnam are as follows: (1) increasing the yield and productivity of crops and livestock by 30%; (2) improving living standards by producing 350-380 kg of grain and 20-22 kg of meat per person; and, (3) increasing the contribution of livestock production to 35% of the total agricultural production.